Fraud Control to Strengthen Internal Control Systems in Local Goverment - Ayu Rakhma Wuryandini; Lukman Pakaya; Siti Pratiwi Husain (AIBPM Publisher, 2023)
Talking about fraud in Indonesia is endless, negligence can lead to fraud, but this fraud can be controlled early with proper internal controls. Fraud will always exist where there are opportunities and weaknesses. Every effort should be made by the organization to prevent and control fraudulent acts. The government agencies in Bone Bolango is a government organization that implements the Fraud Control Plan control tool. The purpose of this research is to analyze the existence and application of the Fraud Control Plan attributes in the work environment of the organization. The research method in this research is descriptive qualitative with a case study at government agencies in Bone Bolango Regency, Gorontalo Province. The results of this study that this government agencies has a good assessment in realizing the performance of Good Governance in the criteria of